A CORRELATIONAL STUDY ON STUDENTS' HABIT OF WATCHING ENGLISH MOVIES AND THEIR MOTIVATION IN SPEAKING ENGLISH AT THE ENGLISH EDUCATION PROGRAM OF STKIP BINA MUTIARA SUKABUMI - Diennur, Usman; Setiawan Muhammad, Aris; Jalianti, Lira; Rusman; Nazmudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigated the correlation between students' habit of watching English movies and their motivation in speaking English at the English Education Program of STKIP Bina Mutiara Sukabumi. A quantitative correlational design was employed involving 20 fourth-semester students selected through purposive sampling. Data were collected using two Likert-scale questionnaires measuring students' habit of watching English movies and their motivation in speaking English. The data were analyzed using descriptive statistics and Pearson Product Moment Correlation with IBM SPSS Statistics. The findings revealed that students demonstrated high levels of both watching habits and speaking motivation. The correlation analysis showed a very strong positive relationship between the two variables (r = 0.886, p < .05), indicating that students who more frequently watched English movies tended to have higher motivation to speak English. The study concludes that habitual exposure to English movies contributes positively to students' motivation in speaking English.